Impact of primary care involvement and setting on multidisciplinary heart failure management: a systematic review and meta‐analysis. (6th January 2021) - Raat, Willem; Smeets, Miek; Janssens, Stefan; Vaes, Bert
Abstract: Multidisciplinary disease management programmes (DMPs) are a cornerstone of modern guideline‐recommended care for heart failure (HF). Few programmes are community initiated or involve primary care professionals, despite the importance of home‐based care for HF. We compared the outcomes of different multidisciplinary HF DMPs in relation to their recruitment setting and involvement of primary care health professionals. We conducted a systematic review and meta‐analysis of randomized controlled trials published in MEDLINE, Embase, and Cochrane between 2000 and 2020 using Cochrane Collaboration methodology. Our meta‐analysis included 19 randomized controlled trials (7577 patients), classified according to recruitment setting and involvement of primary care professionals. Thirteen studies recruited in the hospital ( n  = 5243 patients) and six in the community ( n  = 2334 patients). Only six studies involved primary care professionals ( n  = 3427 patients), with two of these recruited in the community ( n  = 225 patients). Multidisciplinary HF DMPs that recruited in the community had no significant effect on all‐cause and HF readmissions nor on mortality, irrespective of primary care involvement. Studies that recruited in the hospital demonstrated a significant reduction in mortality (relative risk 0.87, 95% confidence interval [CI] [0.76, 0.98]), HF readmissions (0.70, 95% CI [0.54, 0.89]), and all‐cause readmissions (0.72, 95% CI [0.60, 0.87]). However, the difference in effect size between recruitment setting and involvement of primary care was not significant in a meta‐regression analysis. Multidisciplinary HF DMPs that recruit in the community have no significant effect on mortality or hospital readmissions, unlike DMPs that recruit in the hospital, although the difference in effect size was not significant in a meta‐regression analysis. Only six multidisciplinary studies involved primary care professionals. Given demographic evolutions and the importance of integrated home‐based care for patients with HF, future multidisciplinary HF DMPs should consider integrating primary care professionals and evaluating the effectiveness of this model.